Ventilation Performance of Air Duct in Double Loaded Corridor Building: A Case Study - Muhammad S. Ulum; Wenny Arminda; Maqbul Kamaruddin; Widi Dwi Satria (Civil Engineering Journal, 2023)
Buildings with double-loaded corridor types are often found in Indonesia and generally function as offices or lecture rooms. This type of building is popular because of its efficient circulation path to accommodate the movement of occupants. However, a wall separating the room from the corridor makes it impossible to put windows to implement a cross-ventilation system due to acoustic problems. Hence, to achieve indoor thermal comfort, this type of building relies on using an air conditioning (AC) system. However, with the WHO's call to reduce the use of AC during the COVID-19 pandemic, it is necessary to evaluate cross-ventilation in double-loaded corridor buildings to meet comfort standards while still preventing acoustic problems due to noise from corridors and other spaces. The study proposes a new natural ventilation system using air ducts placed above the corridor ceiling to create cross-ventilation in lecture buildings. The E-ITERA building was chosen as a case study in this research. The building has a glass facade with several small windows that can be opened outside. The corridor of this building is designed with openings at both ends, allowing for direct connection to the outside air. The walls facing the passage have a single door and four small ventilations on the aisle's upper side. Simulations were carried out in two classrooms on the 3rd floor using CFD (Computational Fluid Dynamics) software. Experiments were carried out to change the size of the air duct and the size of the ventilation on the wall that leads to the corridor. The results showed that the air duct was able to create cross-ventilation. Ventilation performance is improved when the WWR air duct is the same as the WWR window. The highest air velocity in the centre of the room is 0.6 m/s. Doi: 10.28991/CEJ-2023-09-10-06 Full Text: PDF